Evaluation of Knowledge, Attitude and Practice of Parents of Children with Cardiac Disease about Oral Health - Masoud Fallahinejad Ghajari; Saeid Mojtahedzadeh; Mohammad javad Kharazifard; Nazli Mahdavi; Saeideh Mohtavipour (Islamic Dental Association of Iran, 2014)
Background and Aim: Cardiac patients have different dental needs than healthy individuals and clinicians should be well aware of these differences. The aim of this study was to evaluate and compare knowledge, attitude and practice of parents of children with cardiac disease and healthy children .   Materials and Methods: In this case-control study, data were collected using a questionnaire. The study population consisted of 25 parents of children with cardiac disease and 25 parents of healthy children selected at a pediatric physician office. Both groups were matched in terms of age, gender and parents' educational level. Data analysis was performed using independent sample t-test for knowledge and attitude and Mann Whitney test for practice with α=0.05 .   Results: Based on the parents' responses, knowledge of parents was 45.24±23.29 in the cardiac group and 41.10±20.45 in healthy group. This difference was not statistically significant. Attitude of parents was 79.3%±9.9 in the cardiac group and 78.9%±6.6 in the healthy group. This difference was not statistically significant either. In the cardiac group, 44% brushed two times a day compared with 20% in the healthy group 50% of the cardiac children had never visited a dentist while healthy children had regular dental visits .   Conclusion: In the fields of knowledge and attitude there were no significant differences between two groups, knowledge of parents in two groups was poor but their attitude was positive also practices of parents in the field of children's brushing was good but in the field of attending to dentist was poor .